Quefazeres necessários à docência: imperativos à formação permanente - Silva, Rogeria Novo da (2013)
This dissertation is the result of research that sought to find the quefazeres necessitated the ongoing training process in order to promote a move Creation , by teachers in ways to teach scientifically organized knowledge and considering the cognitive reality of learners . The Freirian categories (1991 , 1996, 1997 , 2005, 2009 ) for ongoing formation , incompleteness quefazeres and supported the theoretical and methodological organization of this research . In the investigation we sought to examine the records of reflections nine teachers from a public school in Pelotas / RS and the training process produced between the years 2009-2012 records . It is worth noting that at first the data were thematized , pointing to a set of considered indicative bounds of teachers in their professional practice, for , in a second moment , be returned to the group for which broaden them. Finally , we performed a semi - structured interview in order to glimpse the possibility of advancing the limits indicated . The reflection data allowed the construction of a conceptual framework in order to support the work of engineers have aimed to consider the process of teacher learning . He excelled as needed quefazeres a) knowledge of the reality of the student, b ) knowledge of the object of knowledge itself , c) knowledge about the learning process ; d ) knowledge about the process of teaching and e ) knowledge of ways of coordinating the processes of teaching and learning in the classroom . From references Paulo Freire , the research allowed still point to ongoing formation as a possibility to consider the ontological vocation of the subjects to be more , and placed with their centrality condition incompleteness , thus advancing to obtaining the necessary autonomy to the professional practice of teaching.